Measurement of the redox state of the plastoquinone pool in cyanobacteria - Khorobrykh Sergey; Tsurumaki Tatsuhiro; Tanaka Kan; Tyystjärvi Taina; Tyystjärvi Esa (John Wiley & Sons Ltd., 2022)
Here, we developed a method for measuring the in vivo redox state of the plastoquinone (PQ) pool
in the cyanobacteria Synechocystis sp. PCC 6803. Cells were illuminated on a glass fiber filter, PQ
was extracted with ethyl acetate and determined with HPLC. Control samples with fully oxidized
and reduced photoactive PQ pool were prepared by far-red and high light treatments, respectively,
or by blocking the photosynthetic electron transfer chemically before or after PQ in moderate
light. The photoactive pool comprised 50 % of total PQ. We find that the PQ pool
of cyanobacteria behaves under light treatments qualitatively similarly as in plant chloroplasts, is
less reduced during growth under high than under ambient CO2 and remains partly reduced in
darkness.